From the age of migration to the decline of migration? : The mobility transition revisited - Peixoto, João (2019)
The main objective of this article is to examine and discuss the current trends of migration and mobility worldwide, as well as the main theories that have been developed to explain them. In addition to a brief state of the art, the article seeks to understand what can happen in the future in the face of global change, whether it is a continuation and deepening of current trends or, on the contrary, a paradigm shift. Despite the greater likelihood of a continuous increase in movements, everything will depend on the confrontation between structural factors and individuals’ agency. If the former present some contradictory signs today, the second reveals the numerous possibilities of action of migrants and non-migrants. There are several possible futures, one of which - the mobility transition - was theorized by Zelinsky in 1971.